Talent attraction and retention through brand building: An exploration of practices in companies that are top South African brands - Wolfswinkel, Michelle (The IIE, 2019)
South African companies, like their global counterparts, are fighting a war for talent, using brand building practices to gain a competitive advantage in attracting and retaining the talented employees required to ensure organisational success. Employer branding with an employee value proposition is used to attract talent, internal brand building is done to engage and retain talent, whilst corporate branding driving purpose and values also plays an important role in both talent attraction and retention. With strategic alignment and consistent branding across employer, internal and corporate branding platforms, talent is optimally attracted and retained as they experience the brand as coherent and trustworthy. Whilst scholars, experts and research studies informed global leading practices in talent attraction and retention through brand building, effective brand building through employer, internal and corporate brand building in South Africa would require an exploration of the local context and the talent target market. Literature outlined several socio-economic factors held to impact attraction and retention of talent through brand building in South Africa.This study therefore set out to explore, in the context of global leading practice, the talent attraction and retention practices pertaining to employer, internal and corporate brand building in companies that are top South African brands. An exploratory study was conducted from the interpretive paradigm using qualitative research methods. Semi-structured interviews were conducted with three strategic-level leaders across five companies that were identified as top South African brands. Fifteen interview transcriptions yielded data in the form of content, which was analysed using inductive reasoning and thematic analysis. Six themes emerged, of which the dominant theme was the value of the corporate brand in talent attraction and retention. Research findings suggest that South African talent are drawn to successful, purposeful and values-based corporate brands. Companies that are top South African brands use this to their advantage, leveraging their corporate brand in talent attraction and retention, with employer and internal brand building practices being less significant and less developed than corporate branding.Findings suggest that, whilst there is a strong perceived relationship between talent attraction and retention and employer, internal and corporate branding, the relationship between talent attraction and retention and corporate branding is particularly strong. The ways in which companies that are top South African brands are attracting and retaining talent through employer, internal and corporate brand building, probed by research question 2, emerged from synthesis of findings, yielding nine local leading practices in talent attraction and retention through brand building. These included talent articulation and assessment; the leveraging of a successful, purposeful and values-based corporate brand; the driving talent engagement and ownership through cross-functional leadership alignment from CEO level downwards; and the use of talent to provide word-of-mouth brand advocacy that builds brand consistency and coherence with all brand stakeholders.The findings from this study add value to the body of current literature, but the real value is in the depth of insight provided to South African companies and their leaders, particularly those in Brand Management and Human Resources or Talent Management.
Keywords: Talent management; Employer brand; Internal brand; Brand coherence; Corporate brand; Brand